2020
DOI: 10.1111/nep.13696
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation and inflammasome activation in human bile cast nephropathy

Abstract: Bile cast nephropathy (BCN) is an underdiagnosed cause of acute kidney injury (AKI).The precise pathogenesis of bilirubin tubular toxicity remains unknown. The aim of this study is to explore the cellular and molecular pathophysiology of human BCN.Paraffin-embedded sections of renal biopsy tissue from a BCN patient were stained by immunohistochemistry (IHC) for oxidative stress (4-hydroxynonenal), immune cell subpopulations, including dendritic cells (CD1c), macrophages (CD68) and T cells (CD3), and inflammaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As an antigen-presenting protein, CD1C can combine lipid and glycolipid antigens and submit them to T-cell receptors on NK-T cells to further activate the immune system (38). While CD1C is rarely expressed in normal kidneys, an increase in its expression has been significantly associated with renal interstitial immune cell infiltration and fibrosis (39,40). A member of the interleukin-1 family, IL33, can bind to IL1RL1/ ST2 receptors to activate the NF-κB and MAPK signaling pathways in Th2 cells, and induce the secretion of type 2-related cytokines in T-helper cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…As an antigen-presenting protein, CD1C can combine lipid and glycolipid antigens and submit them to T-cell receptors on NK-T cells to further activate the immune system (38). While CD1C is rarely expressed in normal kidneys, an increase in its expression has been significantly associated with renal interstitial immune cell infiltration and fibrosis (39,40). A member of the interleukin-1 family, IL33, can bind to IL1RL1/ ST2 receptors to activate the NF-κB and MAPK signaling pathways in Th2 cells, and induce the secretion of type 2-related cytokines in T-helper cells (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have considered the extra-hepatic effects of bile salts on the myocardium, where it was shown that elevated levels of bile salts elicited a negative inotropic and chronotropic effect leading to renal hypo-perfusion [2]. Interestingly, it has been suggested that bile casts may trigger the inflammasome signalling cascade via built up oxidative stress, hence leading to interstitial inflammation and driving bile cast nephropathy pathobiology [5]. Although kidney biopsy is the solitary means of establishing definitive diagnosis, it is often too invasive, or not practical.…”
Section: Discussionmentioning
confidence: 99%